Topologically-guided continuous protein crystallization controls bacterial surface layer self-assembly - Colin J. Comerci (Nature Portfolio, 2019)
Bacteria assemble the surface layer (S-layer), a crystalline protein coat surrounding the curved surface, using protein self-assembly. Here authors image native and purified RsaA, the S-layer protein from C. crescentus, and show that protein crystallization alone is sufficient to assemble and maintain the S-layer in vivo.